Associations of infection control measures and norovirus outbreak outcomes in healthcare settings: a systematic review and meta-analysis. Issue 2 (1st February 2022) - Adams, Carly; Peterson, Shenita R; Hall, Aron J; Parashar, Umesh; Lopman, Benjamin A
ABSTRACT: Background: Although most norovirus outbreaks in high-income countries occur in healthcare facilities, information on associations between control measures and outbreak outcomes in these settings is lacking. Methods: We conducted a systematic review/meta-analysis to assess associations between norovirus outbreak control measures and outcomes in hospitals and long-term care facilities (LTCFs), globally. Using regression analyses stratified by setting (hospital/LTCF), we compared durations, attack rates, and case counts for outbreaks in which control measures were reportedly implemented to those in which they were not. Results: We identified 102 papers describing 162 norovirus outbreaks. Control measures were reportedly implemented in 118 (73%) outbreaks and were associated with 0.6 (95% CI: 0.3–1.1) times smaller patient case counts and 0.7 (95% CI: 0.4, 1.0) times shorter durations in hospitals but 1.5 (95% CI: 1.1-2.2), 1.5 (95% CI: 1.0–2.1) and 1.6 (95% CI: 1.0–2.6) times larger overall, resident and staff case counts, respectively, and 1.4 (95% CI: 1.0–2.0) times longer durations in LTCFs. Conclusions: Reported implementation of control measures was associated with smaller/shorter outbreaks in hospitals but larger/longer outbreaks in LTCFs. Control measures were likely implemented in response to larger/longer outbreaks in LTCFs, rather than causing them. Prospective observational or intervention studies are needed to determine effectiveness.